2022
DOI: 10.3390/bioengineering9010019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Polycaprolactone Electrospun Nanofiber-Composites for Artificial Skin Based on Dermal Fibroblast Culture

Abstract: The study’s aim was to develop a dermal equivalent scaffold that can mimic the architecture and biological performance of the human dermis. Poly ε-caprolactone (PCL) electrospun nanofiber material (ENF) was assembled with polyethylene glycol diacrylate (PEGDA), sodium alginate (SA) and type I collagen (CG1) to develop three groups of dermal equivalent scaffolds. These scaffolds were named PEGDA-PCL, SA-PCL and CG1-PCL. Scanning electron microscopy (SEM) images of cell-free scaffolds’ top and cross-sectional su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…[94] Finally, the studies on skin cell models produced markedly different results compared with the intestinal and lung cell models. Although several studies have shown the potential of pristine PCL [65] and PCL-based electrospun nano/microfibers scaffolds for culturing skin cells, [95][96][97][98][99][100][101] especially in the context of wound healing, few have considered PCL:cellulose composites. [79,[102][103][104][105][106] For example, Huang et al [103] prepared tri-layer nanofibrous scaffolds from PCL, CA, and chitosan that have been shown to promote adhesion, spreading, proliferation, segregation, and basal membrane production of human keratinocytes and fibroblasts…”
Section: Discussionmentioning
confidence: 99%
“…[94] Finally, the studies on skin cell models produced markedly different results compared with the intestinal and lung cell models. Although several studies have shown the potential of pristine PCL [65] and PCL-based electrospun nano/microfibers scaffolds for culturing skin cells, [95][96][97][98][99][100][101] especially in the context of wound healing, few have considered PCL:cellulose composites. [79,[102][103][104][105][106] For example, Huang et al [103] prepared tri-layer nanofibrous scaffolds from PCL, CA, and chitosan that have been shown to promote adhesion, spreading, proliferation, segregation, and basal membrane production of human keratinocytes and fibroblasts…”
Section: Discussionmentioning
confidence: 99%
“…The uniqueness of this study proposed that the dermal equivalent model -PCL collagen based [34] provides a suitable condition to have antibacterial properties as well as drugreleasing (GSH) properties. According to the degradation test, it was not showing any degradation after 10 days in any treated samples.…”
Section: Discussionmentioning
confidence: 99%
“…The translation of this study is to develop the skin equivalent model to add GSH combining with GLU and PBS to see the effect whether it has the antibacterial and drug releasing properties. In our previous study we already developed a collagen PCL based skin equivalent model [34]. In that research study we found that PCL collagen is a suitable model for skin equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the electrospinning has emerged as a promising technique for the preparation of nanofibers with unique properties like flexibility, high porosity, high surface area and aspect ratio. The electrospun nanofibers have shown potential applications in various scientific domains including energy (Sha et al, 2022;Zhu et al, 2022), environment (Kang et al, 2022;Lv et al, 2022), drug delivery (Kang et al, 2020;Li et al, 2022), sensors (Du et al, 2022;Zhang et al, 2022), functional textiles and medicated products (Khandaker et al, 2022;Wu et al, 2022) etc. In the context of nano-delivery systems, the polymer-based nanofibers have emerged as promising carriers for natural molecules, drugs and nanomaterials with wide applications in bioremediation, electrical and biomedical applications etc (Chen et al, 2020;Marinho et al, 2021;Sameen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%